Evaluation of Different Retention Systems on a Distal Extension Removable Partial Denture Associated With an Osseointegrated Implant - Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP]; Falcon-Antenucci, Rosse Mary [UNESP]; Goiato, Marcelo Coelho [UNESP]; Gennari Filho, Humberto [UNESP] (Lippincott Williams & Wilkins, 2010)
The aim of this study was to evaluate the biomechanical behavior of a mandibular distal extension removable partial denture (DERPD) associated with an implant and different retention system, by bidimensional finite element method. Five hemimandible models with a canine and external hexagon implant at second molar region associated with DERPD were simulated: model A, hemimandible with a canine and a DERPD; model B, hemimandible with a canine and implant with a healing abutment associated to a DERPD; model C, hemimandible with a canine and implant with an ERA attachment associated to a DERPD; model D, hemimandible with a canine and implant with an O'ring attachment associated to a DERPD; and model E, hemimandible with a canine and implant-supported prosthesis associated to a DERPD. Cusp tips were loaded with 50 N of axial or oblique force (45 degrees). Finite element analysis was performed in ANSYS 9.0. model E showed the higher displacement and overload in the supporting tissues; the patterns of stress distribution around the dental apex of models B, C, and D were similar. The association between a DERPD and an osseointegrated implant using the ERA or O'ring systems shows lower stress values. Oblique forces showed higher stress values and displacement. Oblique forces increased the displacement and stress levels in all models; model C displayed the best stress distribution in the supporting structures; healing abutment, ERA, and O'ring systems were viable with RPD, but DERPD association with a single implant-supported prosthesis was nonviable.
Keywords: Dental implant; retention systems; removable partial denture; finite element analyses